Effects of the 2018 Japan Floods on long-term care insurance costs in Japan: retrospective cohort study - Shuhei Yoshida; Saori Kashima; Shinya Ishii; Soichi Koike; Masatoshi Matsumoto (BMC, 2022)
Abstract Background Climate change has increased the frequency and severity of torrential rains and floods around the world. Estimating the costs of these disasters is one of the five global research priorities identified by WHO. The 2018 Japan Floods hit western Japan causing extensive destruction and many deaths, especially among vulnerable elderly. Such affected elderly would need long-term care due to the various health problems caused by the disaster. A Long-Term Care Insurance (LTCI) system provides care services in Japan. The aim of this study was to evaluate the effect of the 2018 Japan Floods on LTCI costs and service utilization. Methods The participants of this retrospective cohort study were all verified persons utilizing LTCI services in Hiroshima, Okayama and Ehime prefectures. The observation period was from 2 months before to 6 months after the disaster. We used Generalized Estimating Equations (GEEs) to examine the association between disaster status (victims or non-victims) and the monthly total costs of LTCI service (with gamma-distribution/log-link) by residential environment (home or facility). Among home residents, we also examined each service utilization (home-based service, short-stay service and facility service), using the GEEs. After the GEEs, we estimated Average Marginal Effects (AME) over all observation periods by months as the attributable disaster effect. Results The total number of participants was 279,578. There were 3024 flood victims. The disaster was associated with significantly higher total costs. The AME for home residents at 2 months after was $214 (Standard Error (SE): 12, p < 0.001), which was the highest through the observation period. Among facility residents, the AME immediately after the disaster increased by up to $850 (SE: 29, p < 0.001). The service utilization among home residents showed a different trend for each service. The AME of home-based services decreased by up to − 15.2% (SE:1.3, p < 0.001). The AME for short-stay service increased by up to 8.2% (SE: 0.9, p < 0.001) and the AME for facility service increased by up to 7.4% (SE: 0.7, p < 0.001), respectively. Conclusions The 2018 Japan Floods caused an increase in LTCI costs and the utilization of short-stay and facility services, and a decrease in utilization of home-based services.